A methodological scoping review of qualitative research on LGBTQ + bullying victimization: Implications for diversity, equity, and inclusion. Issue 4 (2nd October 2022) - Newman, Peter A.; Reid, Luke; Lacombe-Duncan, Ashley; Tepjan, Suchon; Ramsundarsingh, Susan
Abstract: We conducted a scoping review in accordance with Cochrane guidelines to identify participant and methodological characteristics of qualitative research conducted with young people on LGBTQ + bullying victimization. From 2005 to 2020, we identified 1, 579 abstracts, with 141 articles retained for full-text screening and 35 included in the review. Overall, participants ( N = 884) were predominantly white (50%), cisgender male (51%), and gay (38%); 14% identified as transgender or gender nonconforming, 13% bisexual, 6% queer or questioning, and 1% asexual. Half of participants identified as ethnic/racial minorities. Most studies (51%) took place in exclusively urban, 17% mixed urban/rural, 3% exclusively rural, and 29% unspecified contexts. Overall, 43% were conducted in the US. Seventeen percent of studies focused exclusively on adolescents under age 18, while 43% excluded this population. Study methodologies included ethnography, grounded theory, phenomenology, and narrative, with nearly one-third unspecified. We outline recommendations for sampling, data collection, and data analysis, researcher self-disclosure, and ethical considerations, for increasing diversity and inclusion in intersectional approaches to LGBTQ + bullying research.